Hyperloop Trial Run: Budgeting Under Uncertainty - Goel, Ganpati; Brahmbhatt, Rahul (Eastasouth Institute, 2025)
The Hyperloop project is a radical new approach to high-speed transportation that could drastically reduce travel times between major cities with little environmental impact. As the project progresses, the trial runs, and promotional events must successfully convince the investor that the technology is feasible to execute the trial runs and promotional events. There are uncertain facts about the technology, the market conditions, and the regulatory difficulties in budgeting for such a complex and innovative System. The challenge for Virgin Hyperloop is to make it through this safely, with careful cost estimation, risk management, and developing a strategic plan. Public-private partnerships, cardio-logical innovations, and scenario-based budgeting are key strategies for sustaining and scaling up. Risk is managed, and the context evolves to meet that need but with long-term funding of project growth in place. Through examining a trial run of Virgin Hyperloop’s promotional scenario and how the financial strategies of Virgin Hyperloop may affect the budgeting process and will be friendly to scale this innovative transportation system, the paper unravels. The other effect of following Hyperloop technology in the world transportation industry became visible.